2004
DOI: 10.2118/84118-pa
|View full text |Cite
|
Sign up to set email alerts
|

High-Power/High-Frequency Acoustic Stimulation: A Novel and Effective Wellbore Stimulation Technology

Abstract: Summary Local impairment of formation permeability often causes reduced production because of the interaction of the reservoir with drilling and completion fluids. The problem may be further compounded by impairment caused by fines migration during production. High-frequency sonic and ultrasonic waves have been used in many industrial applications to remove contaminants, such as dirt, oil, and grease from parts that are immersed in fluids. An obvious extension of this applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Use of vibrations was thus aimed at stimulating the entire borehole wall, including clogged zones. The main difference with previous studies (Champion et al 2004 ; Wong et al 2004 ) is that we used frequencies in the acoustic (200 Hz) instead of ultrasonic range (10,000 Hz) to increase the penetration depth. Tests performed in a formation with similar diameter grainsize had demonstrated that penetration depth increases from several centimeters for ultrasonic stimulation (Bunnik 2004 ) to 10 m for acoustic stimulation (van der Schans et al 2014 ), thus more than enough to reach the borehole wall with a downhole apparatus.…”
Section: Discussionmentioning
confidence: 97%
“…Use of vibrations was thus aimed at stimulating the entire borehole wall, including clogged zones. The main difference with previous studies (Champion et al 2004 ; Wong et al 2004 ) is that we used frequencies in the acoustic (200 Hz) instead of ultrasonic range (10,000 Hz) to increase the penetration depth. Tests performed in a formation with similar diameter grainsize had demonstrated that penetration depth increases from several centimeters for ultrasonic stimulation (Bunnik 2004 ) to 10 m for acoustic stimulation (van der Schans et al 2014 ), thus more than enough to reach the borehole wall with a downhole apparatus.…”
Section: Discussionmentioning
confidence: 97%
“…• Micro-emulsification of oil in the presence of natural or introduced surfactants (Abismail et al 1999), • Coalescence and dispersion of oil drops due to the Bjerknes forces (Bjerknes 1906;Metting et al 1997), • Increase in rock permeability and porosity due to removal of fines and clays, paraffin wax and asphaltenes (Roberts et al 2000;Champion et al 2004;Wong et al 2004;Poesio et al 2004), • Oscillation and excitation of capillary trapped oil drops due to pressure perturbations generated by cavitating bubbles and mechanical vibrations of rock and fluid Higdon 2000a, b, 2002a, b).…”
Section: Oil Recovery Mechanisms Under Sonic Wavesmentioning
confidence: 99%
“…They attributed these findings to the fact that vibrations provide the necessary mechanical force to overcome capillary entrapment, thereby mobilizing oil drops within pores. High power ultrasound may also be applied to reduce formation damage caused by fines and drilling mud solids, and to help mobilize clays in rocks (Venkitaraman et al 1995;Wong et al 2003Wong et al , 2004Roberts et al 2000;Champion et al 2004;Poesio et al 2004), thereby increasing rock permeability and porosity. Venkitaraman et al (1995) conducted a series of laboratory experiments to investigate the feasibility of using ultrasound to remove formation damage caused by water-based drilling mud and fines.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] In contrast, acoustic systems have been shown to be beneficial for removing inorganic plugs, reducing the viscosity of heavy crude oil, and degrading polymer gel structures. [30,[33][34][35][36] Acoustic wave technology is known for its efficient, reliable, convenient, adaptable, and environmentally friendly operations. [37,38] With this method, production engineers can monitor real-time effects and optimize sonication parameters and exposure times.…”
Section: Introductionmentioning
confidence: 99%